MORTAR SEMEN ABU DAUN PINUS DAN ABU BATA MERAH - Elhusna, Elhusna; Afrizal, Yuzuar; Sofia, Halimatus (Inersia: Jurnal Teknik Sipil, 2019)
his article is a report research of mortar with 10% Pine leaf ash (PLA) and 5 variations of red brick ash (RBA). The mortar is a mixture of fine sand, water, and adhesive material with proportion of cement and fine sand is 1 dan 3. RBA was added up to 50% of cement with 10% addition for each variation. Both of the ashes were added base on the weight volume of cement of normal mortar. The normal mortar is the mortar without the ashes. The initial flow of themortar is 105%-115%. The 5 cm mortar cubes were made to test the compressive strength and the absorbtion. The tests were done according to SNI 03-6825-2002 and SNI 15-2049-2004 when the speciments age is 28 days. The cube speciments were taken out of the water sink a day earlier. The highest compressive strength is 22,4% higher than the normal mortar come out ofthe PLA mortar without RBA. The strength of the PLA and 10% RBA mortar is 4,4% higher than the normal one and 18% lower then the PLA mortar without the RBA. The lowest mortar absorbtion (11,68%) belongs to PLA mortar with 10% RBA. The research result shows that the absorbtion and the compressive strength of the mortar isnot always inversely propotional.